Salmonella Phage vB_SpuM_X5: A Novel Approach to Reducing Salmonella Biofilms with Implications for Food Safety - Xinxin Jin; Xiuxiu Sun; Qin Lu; Zui Wang; Zhenggang Zhang; Xiaochun Ling; Yunpeng Xu; Ruiqin Liang; Junjie Yang; Li Li; Tengfei Zhang; Qingping Luo; et al. (Microorganisms)
Salmonella, a prevalent foodborne pathogen, poses a significant social and economic strain on both food safety and public health. The application of phages in the control of foodborne pathogens represents an emerging research area. In this study, Salmonella pullorum phage vB_SpuM_X5 (phage X5) was isolated from chicken farm sewage samples. The results revealed that phage X5 is a novel Myoviridae phage. Phage X5 has adequate temperature tolerance (28 °C–60 °C), pH stability (4–12), and a broad host range of Salmonella bacteria (87.50% of tested strains). The addition of phage X5 (MOI of 100 and 1000) to milk inoculated with Salmonella reduced the number of Salmonella by 0.72 to 0.93 log10 CFU/mL and 0.66 to 1.06 log10 CFU/mL at 4 °C and 25 °C, respectively. The addition of phage X5 (MOI of 100 and 1000) to chicken breast inoculated with Salmonella reduced bacterial numbers by 1.13 to 2.42 log10 CFU/mL and 0.81 to 1.25 log10 CFU/mL at 4 °C and 25 °C, respectively. Phage X5 has bactericidal activity against Salmonella and can be used as a potential biological bacteriostatic agent to remove mature biofilms of Salmonella or for the prevention and control of Salmonella.